Vibration and noise control using shunted piezoelectric transducers: A review. (November 2018) - Gripp, J.A.B.; Rade, D.A.
Highlights: An updated review on piezoelectric transducers combined with shunt circuits is made. The review includes various types of circuits and modeling techniques. Statistics about research papers and patents are shown. A critical evaluation of current achievements and perspectives is made. Abstract: Among various strategies developed for the attenuation of noise and vibration in mechanical structures, piezoelectric shunt damping, which consists in connecting piezoelectric transducers integrated in a structure to electric or electronic circuits, is a promising alternative for use in small- and mid-scale structural components. Despite the fact that the shunt damping technology has been investigated for quite a long time, it is recognized that its application to real-world structures still requires developments aiming at improving its effectiveness and range of application under unavoidable practical constraints. As a result, research on improved solutions related to piezoelectric shunt damping is still very active. Due to the very nature of the piezoelectric shunt damping, it becomes clear that further improvements must consider both mechanical and electrical/electronic aspects. Based on the current state-of-the-art, this paper provides a systematic literature review of different piezoelectric shunt damping strategies developed for the attenuation of vibration and noise in mechanical systems, including an assessment of the basic principles underlying the electromechanical behavior, as well as design procedures and numerical modeling of piezoelectric shunt damping devices applied to elastic vibrating systems. Emphasis is placed on the various types of shunt circuits, including the traditional passive resonant circuits, multimode resonant circuits, adaptive tuning circuits, switching circuits, and negative capacitance. The strategies for location and shape of the piezoelectric transducers is also discussed. A variety of applications recently reported in the scientific literature and in patents are presented. An assessment is made about more significant recent achievements and technological issues to be faced in further developments.